Healthcare beliefs and practices of kin caregivers in South Africa: implications for child survival - Khuthala Mabetha; Nicole C. De Wet-Billings; Clifford O. Odimegwu (BMC, 2021)
Abstract Background Appropriate health-seeking practices may have a positive influence on child survival, particularly when practiced by kin caregivers of children who are below the age of 5 years. While literature has shown that children who are raised in kinship care often present with poor health outcomes and often have unmet healthcare needs, the health-seeking behaviours and practices of the children's kin caregivers that ultimately influence these health outcomes remain largely unknown. In this paper, we explored the healthcare beliefs and practices of kin caregivers in South Africa on child survival. Methods Overall, 12 structured interviews were conducted with all the participants. Six [6] interviews were conducted in the Eastern Cape province and 6 were conducted in the KwaZulu-Natal province. The sample of participants was obtained by seeking permission from the child welfare authorities in the KwaZulu-Natal and Eastern Cape Department of Social Development (DSD) to assist in identifying a sample of the kin-caregivers who have provided primary care to children below the age of 5. The structured interviews were transcribed and analysed using thematic content analysis. After thematic content analysis was carried out, transcripts were given case numbers and then imported into NViVo version 11 for analysis and interpretation of the findings. Results The healthcare seeking behaviours and poor use of healthcare services of the caregivers were largely influenced by their notions and perceptions of health and illness. The notions and perceptions that the caregivers hold about the health statuses of the children placed under their care and illness were found to be largely culturally determined and largely influenced by preconceptions and certain healthcare beliefs. Increased reliance on traditional herbs, Notion of witchcraft and Faith healing emerged as key factors that influence health-seeking practices and beliefs of kin caregivers, thus influencing under-five mortality. Conclusion Kin caregivers should be equipped with the necessary guidance, resources and training that facilitate the successful fulfilment of the caregiving role, given the number of unmet needs and challenges that they face. This will in turn translate into positive child health outcomes.